Fault Tolerance On Binary Vote Assignment Cloud Quorum (BVACQ) Replication Technique - Noraziah, Ahmad; Abdulla Fairuzullah, Ahmad Tajuddin; Ainul Azila, Che Fauzi; Nurzety Aqtar, Ahmad Azuan; Azlina, Zainuddin; Herawan, Tutut (2013)
Replication provides user with fast, local access to shared data, protects availability of applications and support fault tolerance because alternate data access options exist. In this paper, we will manage availability of data replication during failure cases in Cloud using a new proposed algorithm called Binary Vote Assignment on Cloud Quorum (BVACQ). This technique combines the replication and fault tolerant mechanism. The result shows that managing replication and fault tolerance through proposed BVACQ able to preserve data consistency. It also increases the degrees of data availability. This is be cause the missing data from during the server failure has been reconciled and replicated after that server recovered.